Desenvolvimento de mímicos das enzimas superóxido dismutases (SOD) e fotossensibilizadores à base de metaloporfirinas hidrossolúveis do tipo [A3B]3+ ou [A4] 4+ (A = 2-N-alquilpiridínio; B = vanilina ou O-alquilvanilina) - Sarmento Neto, José Ferreira (2021)
Water-soluble Mn(III)-porphyrins and Zn(II)-porphyrins (MnPs ou ZnPs) derived from 2-N-alkylpyridiniumporphyrins, MnTalkyl-2-PyP5+ or ZnTalkyl-2-PyP4+, have been widely explored as redox-active therapeutics or photosensitizers (PSs). The in vivo efficiency of these Mn(III)-porphyrins is related not only to their redox activities (such as superoxide dismutase mimics, or peroxynitrite scavengers) but also their lipophilicity, bioavailability, and toxicity. Based on the structure-activity relationships described for MnTalkyl-2-PyP5+, the design and synthesis of a new class of A3B-type porphyrins (A = 2-pyridyl, B = vanillin or O-alkylvanillin, where alkyl = Me, nPr, nBu, iBu, nHex, nNon, 2-cyclohexylethyl), the methylation of these compounds to yield [A3B]3+ -type cationic porphyrins (H2VanTriM-2-PyP3+ e H2RVanTriM-2-PyP3+; R = Me, nBu, nHex) and the preparation of [MnA3B]4+ -type MnPs (MnVanTriM-2-PyP4+ e MnRVanTriM-2- PyP4+; R = Me, nPr, nHex) were carried out, resulting in 18 new compounds. The chromatographic retention factors (Rf) of these compounds increased linearly with number of carbons in the RVan alkyl group, suggesting that lipophilicity follows a similar trend. The Mn(III)/Mn(II) reduction potential (E½) and the SOD activity (log kcat) of the prototypes MnVanTriM-2-PyP4+ and MnMVanTriM-2-PyP4+ (E½ ~ 110 mV vs NHE; log kcat ~ 6.25) were smaller than those of the [MnA4] 5+ -type MnP analogue MnTM-2-PyP5+ (E½ = 220 mV vs NHE; log kcat = 7.79), being consistent with the structural design resulting from the substitution of an electron-withdrawing group (2-N-methylpyridinium) for an electron-donor group (vanillin or O-methylvanillin), and consequent reduction in electrostatic facilitation, associated with a reduction in the overall charge of these [MnA3B]4+ complexes. Chromatographic data indicated that the lipophilicity of the [MnA3B]4+ compounds is remarkably higher than MnTalkyl-2-PyP5+ analogues. These activities and lipophilicity properties are reminiscent of those of 3-N-pyridylporphyrin based systems, making these [MnA3B]4+ compounds promising candidates for the development of redox-active therapeutics. Additionally, these studies were extended to ZnP systems of interest for the development of PS candidates for antimicrobial photodynamic inactivation (aPDI). The ZnTalkyl-2-PyP4+ (alkyl = Et, nHex) syntheses were revisited and the stability of these ZnPs against solvolysis in acids and simulated biological fluids was evaluated. The stability order, ZnTnHex-2-PyP4+ > ZnTE-2-PyP4+ , reflected the steric hindrance effect of N-alkyl chain toward acid solvolysis and, in both cases, a significant acid-counterion-dependence was observed for ZnP stability: phosphates ≫ nitrate > chloride. The [ZnA3B]4+ -type ZnP ZnMVanTriM-2-PyP3+ was obtained and partially characterized. Chromatographic data for ZnMVanTriM-2-PyP3+ suggested that this ZnP may have similar lipophilicity to the potent, bioavailable [ZnA4] 4+ PS meso-tetrakis(N-n-butylpyridinium-2-yl)porphyrinatezinc(II) (ZnTnBu-2-PyP4+). ZnTE-2-PyP4+ and ZnTnHex-2-PyP4+ showed excellent photosensitizing properties in aPDI of both promastigote and amastigote forms of Leishmania genus parasites. The higher PS activity of ZnTnHex-2-PyP4+ was associated to its higher lipophilicity.